"A Jack of Trio"-robust one-pot metal free oxidative amination, azidation and peroxidation of phenols. (24th April 2017) - Sarkar, Debayan; Ghosh, Manoj Kumar; Rout, Nilendri; Kuila, Puspendu
Abstract : Facile generation of quaternary carbon centres has been realised in the presence of phenyl trimethyl ammonium tribromide (PTAB) mediated oxidative dearomatisation. Abstract : Herein we disclose a highly efficient methodology for the generation of nitrogen containing quaternary carbon centres via aminative and azidative oxidative dearomatization of phenols. The same protocol has also been successfully employed to achieve oxidative peroxidation of phenols. The simplest metal free reaction conditions delineate an easy breakthrough to the " Trio "- oxidative amination, azidation and peroxidation. An array of diverse polyfunctionalised heterocycles has been synthesized in one pot.